The Effect of Fit and Company’s Motivation on Consumers’ Evaluation of Cause Related Marketing - CHEN, YUN-PING (2011)
Cause Related Marketing has increasingly became a prevalent and meaningful part of a company’s marketing plan. A successful Cause Related Marketing campaign can create a win-win-win situation for companies, customers and non-profit organisations.